Pengaruh Adverse Selection, Kontrol Monitoring, Dan Penalaran Moral Individu Terhadap Perilaku Eskalasi Komitmen - Nayang Helmayunita (Universitas Negeri Padang, 2015)
This study aims to examine the effects of adverse selection in the escalation of commitment and the effectiveness of monitoring control and the moral reasoning managers in de-escalating of commitments. The research design was a 2x2 laboratory experiments, with students accounting State University of Padang as a proxy for the project manager. Each subject was presented one of four versions available cases randomly (random assignment). The statistical method is used to test the hypothesis is two-way ANOVA. The results showed that the conditions of adverse selection decision has no effect on project evaluation, monitoring controls have an influence on project evaluation decisions, and the interaction between adverse selection conditions and monitoring control not to cause differences in decision making managers in evaluating projects that are not profitable. In conditions of adverse selection, there is a difference in the decision-making managers who have a high level of moral reasoning with managers who have low level the moral in evaluating projects that are not profitable, and on the condition of adverse selection, there was no difference in manager’s with the a low level of moral reasoning who received monitoring control and did not get the monitoring control from the company in evaluating investment projects unprofitable. Keywords: escalation of commitment, monitoring control, adverse selection, moral reasoning.